2015
DOI: 10.1021/acs.nanolett.5b03485
|View full text |Cite
|
Sign up to set email alerts
|

High Quantum Efficiency Nanopillar Photodiodes Overcoming the Diffraction Limit of Light

Abstract: InAs1-xSbx nanowires have recently attracted interest for infrared sensing applications due to the small bandgap and high thermal conductivity. However, previous reports on nanowire-based infrared sensors required low operating temperatures in order to mitigate the high dark current and have shown poor sensitivities resulting from reduced light coupling efficiency beyond the diffraction limit. Here, InAsSb nanopillar photodiodes with high quantum efficiency are achieved by partially coating the nanopillar with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 32 publications
2
57
0
Order By: Relevance
“…For 3D nanostructured photodetectors, specific SPs structures are needed to fit the light coupling to nanostructures beyond planar films. Recently, Lee et al reported a partial metal cover that accommodate near‐field enhancements to the photodetector based on InAsSb nanopillar (NP) arrays (Figure c–e) . As mentioned earlier, NW or NP based photodetectors exhibit much lower dark currents compared to planar devices.…”
Section: Surface Plasmon Resonance Enhanced Infrared Photodetectorssupporting
confidence: 86%
See 1 more Smart Citation
“…For 3D nanostructured photodetectors, specific SPs structures are needed to fit the light coupling to nanostructures beyond planar films. Recently, Lee et al reported a partial metal cover that accommodate near‐field enhancements to the photodetector based on InAsSb nanopillar (NP) arrays (Figure c–e) . As mentioned earlier, NW or NP based photodetectors exhibit much lower dark currents compared to planar devices.…”
Section: Surface Plasmon Resonance Enhanced Infrared Photodetectorssupporting
confidence: 86%
“…e) The photoresponse spectra of the photodetector, the peak at ≈2390 nm is ascribed to SPs induced near‐field enhancement. Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: Surface Plasmon Resonance Enhanced Infrared Photodetectorsmentioning
confidence: 99%
“…Since compact circular‐polarization‐discriminative devices are highly desired for infrared detection, we investigate the integration of an InAsSb nanowire array with an asymmetric metamaterial. An InAsSb nanowire array is a promising candidate for infrared detection [ 41,48–50 ] because of the tunable band gap, the heteroepitaxial growth, and the release of lattice mismatch strain through radial expansion instead of defect creation. [ 51–53 ] The relative composition of As and Sb in the InAs 1‐ x Sb x nanowires is chosen to be 0.4 and 0.6 for mid‐wavelength to long‐wavelength infrared detection.…”
Section: Figurementioning
confidence: 99%
“…The stronger photoresponse at λ = 780 nm may be from the higher absorption attributed by the tightly confined mode on top of the NW supported by the LSP resonance at the edge of the metal cap. 25 The inset shows the detector has a linear photoresponse up to 4 mW at λ = 1310 nm under 0 V. The infrared photoresponse and the linearly increase photovoltaic current at 0 V from the detector suggests the trap states at the InAs/Si heterojunction does not limit the flow of the photocurrent. The photogenerated electrons are collected from the InAs NW top contact and the holes from Si substrate can overcome a small valance band barrier into the InAs NW.…”
Section: 23mentioning
confidence: 99%
“…In addition our didoes show a comparable photocurrent level compared to the reported InAs NW detector with similar NW height. 30 We expect an increased absorption efficiency of the InAs/InAsP NW array detector by appropriate optical design of the NW length and diameter 25 and improving the growth yield to form ordered NW array.…”
Section: Research Article Nano Advancesmentioning
confidence: 99%